Pro PHP and jQuery - Lengstorf, Jason (Apress, 2012)
To fully understand jQuery and its applications in modern web programming, it's important to take a moment and look back at where jQuery came from, what needs it was built to fill, and what programming in JavaScript was like before jQuery came around. In this chapter you'll learn about JavaScript libraries and the needs they seek to fulfill, as well as why jQuery is the library of choice for the majority of web developers. You'll also learn the basics of jQuery, including how to make the library available for use in your applications and how the core of jQuery—its powerful selector engine—works.